Comparison of body density and precent body fat as computed using four different lung volumes in the hydrostatic weighing technique - Witherspoon, Dean (My University, 1984)
This study compared body density (BD) and percent body fat (%BF) arrived at by using four different lung volumes in the hydrostatic weighing (HW) procedure. The four lung volumes were residual volume as measured in air (RV-dry), residual volume as measured immersed in water (RV-wet), functional residual capacity,as measured immersed (FRC), and total lung capacity as measured immersed (TLC). The closed circuit oxygen dilution technique was used to measure all lung volumes.
Keywords: Human body, Density. Measurement.